Coagulante orgânico Moringa oleífera como alternativa ao uso do coagulante inorgânico sulfato de alumínio no tratamento de água - Silva, Larissa Botura da (2017)
In order for the water to be considered adequate for consumption, in accordance with the potability standards established by Ministry of Health Ordinance 2914/2011, it is necessary that it undergo treatment processes that occur within the water treatment plants (ETAs) and, after it is apt to be distributed to the population. One of the treatment processes is coagulation, where the particles in suspension are removed with the aid of a coagulant, usually the most used are of chemical origin, such as aluminum sulfate. Moringa oleifera is an organic coagulant used for the treatment of water as one of the alternative techniques, replacing os complementing inorganic coagulants. The objective of this work was to determine and compare the characteristics of the water generated in the coagulation/flocculation/sedimentation/filtration process using both the Moringa oleifera organic coagulant and the inorganic aluminum sulfate coagulant. By means of Jar-Test tests followed by direct down-flow filtration using sand filters, three treatments were performed (A1- Application of 100% of Moringa oleifera; A2- Application of 100% of aluminum sulfate; and A3- Applicate of 50% of Moringa oleifera + 50% of aluminum sulfate). The analyzed parameters were: electrical conductivity; apparent color; turbidity; pH; temperature; total coliforms and Escherichia coli (E. coli). The results obtained for the temperature did not presente significant change in any treatment, remaining between 24°C and 27°C, as well as the pH, which remained within the standards required by Ministry of Health Ordinance 2914/2011. The electrical conductivity increased, reaching 0.40 mS.cm¯¹, in the A1 treatment, due to the release of ionic species by the organic coagulant, while for the other treatments, the parameter remained the same as the value obtained for the raw water. In relation to the removal efficiency of the analyzed parameters, the organic coagulant removed after filtration 73,37% of the apparent color, 94,74% of the turbidity, and 99,72% of E. coli. The A2 treatment showed removal efficiency of 97,09% for apparent color, 92,69% for turbidity, and 89,54% for E. coli, while A3 treatment removed 42,28%, 91,46% and 23,43%, respectively. In the statistical analysis, the comparison of means by Tukey’s test showed that, for most of the trials, the interaction between Coagulant*Time did not present a significant effect, indicating that the time effect did not vary significantly as a function of the coagulants, mainly for the coagulante organic. Although they have close percentages of removal, the positive results make it preferable to use organic coagulant instead of aluminum sulfate, since it is of natural origin, has low cost and does not cause negative effects to the environment and humans, making a potential alternative for the treatment of water for supply.